Scandal mining: political nobodies and remediated visibility. (September 2018) - Trottier, Daniel
This article considers the 2015 federal election in Canada as the emergence of seemingly citizen-led practices whereby candidates' past missteps are unearthed and distributed through social and news media channels. On first pass, these resemble citizen-led engagements through digital media for potentially unmappable political goals, given the dispersed and either non-partisan or multi-partisan nature of these engagements. By bringing together journalistic accounts and social media coverage alongside current scholarship on citizenship and visibility, this case study traces the possibility of political accountability and the political weaponisation of mediated visibility through the targeted extraction of candidate details from dispersed profiles, communities and databases.